Menguak misteri ajaran agama agama besar - H.M. Arifin (Golden Terayon Press, 1997)
ws.c.1/ir,c.2,3/oen, c.4-7/ir,c.8/sgh,c9/ir,c.10; nr c.11/oen, c.12/sgh c 13/oen, c.14-15/ir,c.16/nr,c.17/ir,c.18/ir,c.19/tr, c.20/stc11,c.1-18/stoc5.c.19